Efektivitas Penggunaan Media Interaktif Flat Panel Terhadap Hasil Belajar Materi Bangun Datar Mata Pelajaran Matematika Kelas IV MI Tarbiyatul Islamiyah Soko Puluhan - Asrul Khodri; Anista Ika Surachman (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
Geometry learning in Islamic elementary schools (Madrasah Ibtidaiyah) often faces challenges related to verbally delivered instruction and limited digital infrastructure. To address these issues, this study examined the effectiveness of Interactive Flat Panel (IFP) media in improving the mathematics learning outcomes of fourth-grade students at MI Tarbiyatul Islamiyah Soko Puluhan. A quantitative research method employing a True Experimental design with a Posttest-Only Control Group was applied to 37 students divided into two groups: an experimental group (n=19) and a control group (n=18). An objective test instrument was used to measure students’ learning outcomes, while data analysis was conducted using the Independent Sample T-Test. The statistical analysis revealed that the mean score of students in the experimental group (80.00) was significantly higher than that of the control group (68.33). The obtained Sig. (2-tailed) value was 0.048, which was lower than 0.05, indicating that the use of IFP had a significant effect on improving learning outcomes. Therefore, this study concludes that the utilization of interactive hardware is effective in visualizing abstract mathematical concepts and equalizing students’ abilities, making it a major recommendation for the provision of digital facilities in madrasah.